KINERJA Saccharomyces cerevisiae REKOMBINAN [GLO1] DALAM PROSES SIMULTAN HIDROLISIS PATI DAN FERMENTASI UNTUK PRODUKSI BIOETANOL - Afaf Baktir; Nur Cholifah; Sri Sumarsih (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Recent development in fermentations for bioethanol production were focused three factors, i.e. abundance and cheap substrates,superior yeast fermenting the substrates, and simultaneous saccharification and fermentation (SSF) technology.Nowadays national and world bioethanol production still depend on sugar cane and starchy materials.This research aims to determinate the optimum simultaneous saccharification and fermentation (SSF) conditions to identify the performance of local strain Saccharomyces cerevisiae recombinant [GLO1] in the producing bioethanol from starch.The optimum conditions for SSF process are in a media composition containing glucose 2% (w/v), starch 5% and at aeration rate 50 rpm.At these optimum conditions Saccharomyces cerevisiae recombinant [GLO1] produce 25.36% (v/v) bioethanol at day-20 of the fermentation process design.